Traumatic Brain Injury in Community Corrections: Prevalence and Differences in Compliance and Long-Term Outcomes Among Men and Women on Probation - Gorgens, Kim A. (Criminal justice and behavior, 2021)
There are 4.5 million adults in community corrections (e.g., probation and parole), nearly twice the number of people incarcerated in jails and prisons combined. Research suggests that more than half of men in jail have experienced at least one traumatic brain injury (TBI). Very little is known about TBI history in probation. This study reviewed TBI history, cognitive and psychosocial data, and judicial records. Results showed that 47% of persons on probation report TBI. People on probation with TBI also had comorbid behavioral health conditions like mental illness, substance abuse, trauma history, and attempted suicide. They were more likely to be determined to be high risk by probation officers, had a higher rate of felony convictions, had lower rates of successful probation completion, and were significantly more likely to re-offend. Attention to responsivity factors like TBI may help probation provide accommodations that support successful engagement in probation and treatment.